Thermoelectricity in correlated narrow-gap semiconductors. (10th April 2018) - Tomczak, Jan M
Abstract: We review many-body effects, their microscopic origin, as well as their impact on thermoelectricity in correlated narrow-gap semiconductors. Members of this class—such as FeSi and FeSb2 —display an unusual temperature dependence in various observables: insulating with large thermopowers at low temperatures, they turn bad metals at temperatures much smaller than the size of their gaps. This insulator-to-metal crossover is accompanied by spectral weight-transfers over large energies in the optical conductivity and by a gradual transition from activated to Curie–Weiss-like behaviour in the magnetic susceptibility. We show a retrospective of the understanding of these phenomena, discuss the relation to heavy-fermion Kondo insulators—such as Ce3 Bi4 Pt3 for which we present new results—and propose a general classification of paramagnetic insulators. From the latter, FeSi emerges as an orbital-selective Kondo insulator. Focussing on intermetallics such as silicides, antimonides, skutterudites, and Heusler compounds we showcase successes and challenges for the realistic simulation of transport properties in the presence of electronic correlations. Further, we explore new avenues in which electronic correlations may contribute to the improvement of thermoelectric performance.